2014
DOI: 10.1002/hbm.22462
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of sensorimotor oscillations is altered in children with hemiplegic cerebral palsy: A magnetoencephalographic study

Abstract: Cerebral palsy (CP) is characterized by difficulty in control of movement and posture due to brain damage during early development. In addition, tactile discrimination deficits are prevalent in CP. To study the function of somatosensory and motor systems in CP, we compared the reactivity of sensorimotor cortical oscillations to median nerve stimulation in 12 hemiplegic CP children vs. 12 typically developing children using magnetoencephalography. We also determined the primary cortical somatosensory and motor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 60 publications
6
43
0
2
Order By: Relevance
“…Our results indicate that the somatosensory cortical oscillations in the beta frequency range were abnormal in the children with CP, while alpha-theta responses seemed relatively intact. Similar exploratory results for the beta frequency were recently reported for a cohort of children with hemiplegic CP that underwent a median nerve stimulation paradigm (Pihko et al, 2014). Together these results imply that aberrations in somatosensory beta oscillatory activity may play a role in the tactile discrimination deficiencies often seen in children with CP.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our results indicate that the somatosensory cortical oscillations in the beta frequency range were abnormal in the children with CP, while alpha-theta responses seemed relatively intact. Similar exploratory results for the beta frequency were recently reported for a cohort of children with hemiplegic CP that underwent a median nerve stimulation paradigm (Pihko et al, 2014). Together these results imply that aberrations in somatosensory beta oscillatory activity may play a role in the tactile discrimination deficiencies often seen in children with CP.…”
Section: Discussionsupporting
confidence: 85%
“…These studies have identified that the somatosensory evoked-potentials/fields for the hand are diminished, and in some cases latent in children with CP (Kulak et al, 2005; Kulack et al, 2006; Riquelme and Montoya, 2010; Teflioudi et al, 2011; Maitre et al, 2012; Pihko et al, 2014; Papadelis et al, 2014). We have previously reported similar results for the foot (Kurz and Wilson, 2011; Kurz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the interactions within the sensorimotor network are also disturbed (27). A recent study employed a multimodal neuroimaging approach and showed changes in somatotopy in cerebral palsy children (28).…”
Section: Discussionmentioning
confidence: 99%
“…Por outro lado, a EMT tem sido utilizada na PC para realizar mapeamento cerebral, determinando o tipo/padrão de organização cortical. A EMT de pulso simples, em associação com a imagem por ressonância magnética (IRM), foi empregada na análise do mapeamento cerebral e avaliação da função da mão de indivíduos com PC unilateral 42,43,44,45,46 . A EMT parece mostrar-se um recurso importante para obter um prognóstico precoce nessa população 44,45 .…”
Section: Artigo De Revisãounclassified